INFLUENCE OF TELEVISION COSMETIC ADVERTISEMENTS ON COSMETICS CONSUMPTION AMONG COLLEGE STUDENTS - S. Vijayalakshmi; Dr.M. Anuradha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
TV commercials are one of the best tools to communicate a large population about the products especially, in the area of marketing than other tools or ways. They are unique because they have visual and audio elements. Therefore, they are effectively used by cosmetic merchandise. They help in creating an excellent image for the products and brands among the consumers. They are playing the role of an informer about the products, their basic applications and additional features and they provide a detailed picture to the consumers also. In this context, this research paper will explore about (i) to find out the role played by TV advertisements in the case of cosmetic consumption. (ii) To find out what are the other factors influence the consumers towards cosmetics consumption. This research study adopts a quantitative research method in the form of a survey.